Optimisation of Data Management System: Development of Requirements - Zivitere, Marga; Almar, Nika (Economics and Business, 2020)
The paper deals with the management of product information in a cosmetics retail and information interaction of a retailer with distributors and manufacturers. We developed a list of requirements for the types of information for a product catalogue. Using a survey and questionnaire of employees of the retailer, we determined what information the departments needed. We made sure that one standard to the structure of information did not exist and proposed our own scheme. Based on the survey results, we created a list of requirements for the information management system and proposed a scheme of system components. We conducted a comparative analysis of the costs of the company (about 2000 employees) for the salary of employees involved in entering information before and after the implementation of our system. For evaluation of the effectiveness of the integration of the developed system, we defined the cost indicators: PP, NPV and IRR.